(3GdeMGSHI GdeGdjI (B:s (3GdbjGS hGdJbhje hGdEaUGM GdeMGSHj (B/s - (3CHh GdecGQe, hUaj YHO GdaJGMs ((3GdEScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 1996)
(3GdeONd GdfXQj dOQGSI GdeMGSHI GdeGdjI, GdOhQI GdeMGSHjI hJOab GdHjGfGJ aj GdhMOGJ GdJLGQjI hGdUfGYjI, GdbhGFe GdeGdjI GdJj JUOQgG GdhMOGJ GdGbJUGOjI, bjGS hJbhje YfGUQ QCS GdeGd GdYGed, bjGS hJbhje GdCUhd hGdGdJRGeGJ WhjdI GdCLd, eTGcd GdGYJQGa HGdGjQGO aj HYV GdCfTWIs
Keywords: (3GdeMGSHI GdJMdjdjIs